(untitled) (Research, Society and Development, 2021)
Soda is a highly consumed aerated mixture due to its practicality and consumer acceptance. However, the consumption of this drink, which often takes place directly on the packaging, makes the product a possible way of proliferation of microorganisms, bringing risks of contamination and transmission of Foodborne Diseases. Thus, the present study aimed to evaluate the microbiological quality of the surface of soda cans. Twenty samples were evaluated, being ten collected from street vendors and ten obtained in supermarkets in the city of Mossoró, Rio Grande do Norte, with investigation of the possible presence of coliforms, Salmonella sp., molds and yeasts. The results showed that 75% of the samples were contaminated by total coliforms, 10% had thermotolerant coliforms, 5% contained Salmonella sp. and that 100% had surface contamination from molds and yeasts. The surfaces of the soda cans presented unsatisfactory hygienic and sanitary conditions for marketing and consumption, requiring the implementation of good handling practices in order to minimize the risk of transmission of Foodborne Diseases.